Pengaruh Motivasi Ekstrinsik dan Komunikasi terhadap Loyalitas Karyawan dengan Komitmen Organisasi sebagai Variabel Mediasi pada CV Twin Setia Yogyakarta - Novita Sari; Prayekti Prayekti (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to determine the effect of extrinsic motivation and communication on employee loyalty with organizational commitment as intervening variables. This type of research is quantitative research. The population is all employees at CV TWIN SETIA, Sewon Subdistrict, Panggungharjo, Sewon, Bantul, Yogyakarta. The sample is 44 samples or 44 respondents. Sampling techniques use saturated sampling techniques. The data collection method in this study was a questionnaire distributed to all employees of the CV TWIN SETIA. The data analysis techniques used multiple descriptive analysis, classic assumption test, linear regression, t test (partial), and coefficients of determination (R2). The results of this study showed that the influence of extrinsic motivation and communication on employee loyalty with organizational commitment as an insignificant variable mediating, communication had a significant positive effect on organizational commitment, and extrinsic motivation had a significant positive effect on employee loyalty. Keywords: Extrinsic Motivation, Comunication, Organizational Commitment, Employee Loyalty